Childhood Varicose Veins–An Unusual Visceral “May–Thurner” Like Compression - Raju, Sreenivasa Narayana; Rajagopal, Rengarajan; Pandey, Niraj; Singh, Amarinder; Kumar, Sanjeev (Journal of Clinical Interventional Radiology ISVIR, 2021)
We report the case of 8-year-old girl with left lower limb edema due to superficial venous incompetence and varicosities. Color Doppler demonstrated compression of the left common iliac vein by an ectopic left kidney, which was partly relieved in right lateral decubitus position. CT demonstrated ectopic malrotated pelvic kidney, compressing the left common iliac vein against the L5 vertebra. A “May–Thurner” like syndrome due to visceral compression needs to be suspected in children with unilateral left lower limb varicosities.
Keywords: May–Thurner syndrome; congenital ectopic kidney; common iliac vein compression